2020
DOI: 10.1186/s12885-020-6645-6
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a predictor of mortality in women with breast cancer: a meta-analysis and systematic review

Abstract: Background: Breast cancer is the most commonly diagnosed cancer and the leading cause of cancer death in women worldwide. Recently, studies have been published with inconsistent findings regarding whether sarcopenia is a risk factor for mortality in breast cancer patients. Therefore, the aim of this systematic review and meta-analysis was to systematically assess and quantify sarcopenia as a risk factor for mortality in breast cancer patients. Methods: In a systematic literature review of PubMed, EMBASE, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 45 publications
3
100
2
Order By: Relevance
“…Previous literature have identified significant associations in patients with lung cancer [ 10 ], head and neck cancer [ 11 , 18 ], GI cancer [ 9 , 19 , 20 ], liver cancer [ 9 , 21 , 22 ], pancreatic cancer [ 23 ], and urinary tract cancer [ 24 ], with largely consistent effect sized identified in the current meta-analysis. However, other recently published meta-analyses by Zhang et al [ 25 ], Ubachs et al [ 26 ], and Jia et al [ 27 ] have identified a significant association between sarcopenia and survival in breast cancer, ovarian cancer, and hematological malignancies, respectively, contrary to insignificant association identified in the current meta-analysis. The inconsistencies are likely due to fewer studies being included in our subgroup analysis, which could be attributed to differences in search strategy.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous literature have identified significant associations in patients with lung cancer [ 10 ], head and neck cancer [ 11 , 18 ], GI cancer [ 9 , 19 , 20 ], liver cancer [ 9 , 21 , 22 ], pancreatic cancer [ 23 ], and urinary tract cancer [ 24 ], with largely consistent effect sized identified in the current meta-analysis. However, other recently published meta-analyses by Zhang et al [ 25 ], Ubachs et al [ 26 ], and Jia et al [ 27 ] have identified a significant association between sarcopenia and survival in breast cancer, ovarian cancer, and hematological malignancies, respectively, contrary to insignificant association identified in the current meta-analysis. The inconsistencies are likely due to fewer studies being included in our subgroup analysis, which could be attributed to differences in search strategy.…”
Section: Discussioncontrasting
confidence: 93%
“…Then, we chose the newest meta‐analysis with the largest number of studies. Finally, 54 health‐related outcomes extracted from 30 meta‐analyses 10,22‐50 were reported in this umbrella review. These 54 outcomes were mainly about prognostic outcomes of tumor, postoperative outcomes, age‐related outcomes, metabolic outcomes, and other outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Around 30-50% of cancer-associated deaths are due to cachexia. During this process, metabolic changes occur; cancer cells behave like parasites, taking nutrition from the surrounding tissue leading to exhaustion of the body's energy resources [229]. Cancer-associated cachexia not only increases the rate of mortality but is also responsible for treatment failure [230,231].…”
Section: Cachexiamentioning
confidence: 99%